Post war reconstruction of the iron and steel trades, 1944 (United Kingdom, 1944)
1944 1939-1945 "Post war reconstruction of the iron and steel trades, 1944" [HFR0084], 1944 This pamphlet by John Brown, General Secretary of the Iron and Steel Trades Confederation, outlines a plan for the public ownership or nationalisation of the iron and steel industry after the war.